Floating wave energy harvester: a new perspective - Deligianni, Angeliki; Drikos, Leonidas (Frontiers in Energy Research, 2023)
Sustainable development principles have brought forth the imperative to harness renewable energy sources to conserve our fragile ecosystems. Among the various renewable energy options, ocean wave energy has garnered significant global interest and is now poised as a leading contender. However, current wave energy collection methods suffer from limitations and technical immaturity, thereby necessitating the need for a more advanced and innovative solution. This paper presents a concept for the development of a floating wave harvester, which aims to convert the energy of ocean waves into usable electrical energy. The focus of this document is to outline the methodology behind the design and construction of the harvester’s buoys, which play a crucial role in determining the overall effectiveness of the system. The buoy shape and material choice are critical to the harvester’s dynamic behavior, energy absorption capacity, and the ability to transform wave kinetic energy into direct and indirect electrical energy. The primary objectives of this ongoing research project are to define the system requirements and specifications and to implement these through practical application. The development of this floating wave harvester holds the potential to significantly contribute to the renewable energy landscape and make significant strides in sustainable development.